Anomalous Behaviour of cis-Bicyclo[3.3.0]octane-3,7-dione and Its Derivatives During Twofold Fischer Indole Cyclization Using Low-Melting Mixtures - Kotha, Sambasivarao; Chinnam, Ajay Kumar (Synthesis, 2014)
We have developed an efficient method for the synthesis of the pentaleno[2,1-b:5,4-b′]diindole and pentaleno[2,1-b:5,6-b′]diindole skeletons via twofold Fischer indole cyclization. In this new procedure, cis-bicyclo[3.3.0]octane-3,7-dione on treatment with 1-methyl-1-phenylhydrazine in the presence of a low-melting mixture of l-(+)-tartaric acid and N,N′-dimethylurea at 70 °C undergoes a twofold Fischer indole cyclization to deliver the unusual Cs-symmetrical product pentaleno[2,1-b:5,6-b′]diindole, along with the expected C2-symmetrical pentaleno[2,1-b:5,4-b′]diindole product.
Keywords: Weiss–Cook condensation; Fischer indole cyclization; low-melting mixture; cis-bicyclo[3.3.0]octane-3,7-dione; heterocycles